HIV and AIDS in the tapestry of meanings : towards understanding perceptions of AIDS by men in a rural community - Mboweni, George Shakespeare (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil (Sociology and Social Anthropology))--Stellenbosch University, 2008.